1994
DOI: 10.1111/j.1365-2621.1994.tb14665.x
|View full text |Cite
|
Sign up to set email alerts
|

Carrot Juice Color, Carotenoids, and Nonstarchy Polysaccharides as Affected by Processing Conditions

Abstract: Effects of processing variables on color, α‐ and β‐carotenes, and non‐starchy polysaccharides (NSP) of carrot juice products were investigated. Unblanched‘carrots produced the highest amounts of juice and lowest amounts of pulp. Compared to color of fresh juice, canned juice from acetic acid‐blanched carrots retained redness best, and juice from unblanched carrots retained the least. Juice products from unblanched carrots retained highest total carotenes. Retorting, concentrating, and freeze‐drying partly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 11 publications
2
33
0
1
Order By: Relevance
“…Caropak (a-carotene, 5.2 mg/ 100 g of fresh matter; b-carotene, 27.7 mg/100 g) ( Table 1). The carotenoid content of all three carrot varieties was higher than that reported by Bao and Chang [7], and comparable with the provitamin A content of the varieties studied by Umiel and Gambelman [9]. These authors found out that the b-carotene content of some carrot varieties may be as high as 37 mg/100 g of fresh matter [7,9].…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Caropak (a-carotene, 5.2 mg/ 100 g of fresh matter; b-carotene, 27.7 mg/100 g) ( Table 1). The carotenoid content of all three carrot varieties was higher than that reported by Bao and Chang [7], and comparable with the provitamin A content of the varieties studied by Umiel and Gambelman [9]. These authors found out that the b-carotene content of some carrot varieties may be as high as 37 mg/100 g of fresh matter [7,9].…”
Section: Resultssupporting
confidence: 77%
“…The content of a-and b-carotene was expressed in mg % of fresh matter. The amount of a-and b-carotene in carrots after hydrothermal processing was also expressed in %, in relation to the amount of carotenoids in raw material, according to the formula given by Bao and Chang [7]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrot cubes (1 cm  1 cm  1 cm) were prepared by a manual dicer and were washed with fresh water to remove the surfaceadhering carrot fines. No blanching was done prior to osmosis as it is detrimental to the osmotic dehydration process due to loss of semi-permeability of cell membranes (Ponting, 1973) and reduction of b-carotene (Bao & Chang, 1994;Kalra, 1990;Negi & Roy, 2000). For each experiment, known weights of carrot cubes (100-120 g) were put into stainless steel containers containing calculated volumes of osmotic solutions of different concentrations pre set at the desired temperature in a hot water bath.…”
Section: Preparation Of Samples and Osmotic Dehydrationmentioning
confidence: 99%
“…Alpha and beta-carotene (dry basis), and vitamin A activity (IU/g, dry basis) were highest in fresh carrots while sweet potatoes and collard greens contained similar amounts of alpha carotene (Table 1). Previous researchers [33,34] have stated that carrots contain the highest total carotene content among human foods. Carrots and collard greens contained more beta-carotene and vitamin A activity (dry basis) than sweet potato (Table 1).…”
Section: Properties Of Fresh Vegetablesmentioning
confidence: 99%